Novel Benzo[f]coumarin Derivatives as Probable Acetylcholinesterase Inhibitors: Synthesis, In Vitro, and In Silico Studies for Evaluation of Their Anti-AChE Activity - Zaizafoon Nabeel; Qassim Abdul-Hussein Jaber; Nabeel Abed Abdul-Rida (Indonesian Journal of Chemistry, 2022)
Novel benzo[f]coumarin derivatives bearing pyrimidine unit were successfully synthesized. The target is to develop novel acetylcholinesterase inhibitors. The benzo[f]coumarin chalcone 4 was prepared via Claisen-Schmidt condensation between 3-acetyl-5,6-benzocoumarin and 4-hydroxybenzaldehyde in the alkaline medium. Then, the cyclocondensation of chalcone 4 with urea, thiourea, and guanidine HCl in the presence of glacial acetic acid led to the formation of various pyrimidines. Structures of the newly synthesized compounds were characterized by FT-IR, 1H-NMR, 13C-NMR spectra, and elemental analysis. The acetylcholinesterase (AChE) inhibitory activity tests were carried out using Ellman's assay and donepezil as a reference drug. The biological activity results revealed that the derivatives 6 and 7 inhibit AChE activity in healthy samples showed that the greater inhibition percentage was found respectively at concentrations of 10–4 and 10–10 M while low inhibition percentage was obtained at 10–12 and 10–4 M. AChE showed inhibition constant Ki in the range of 10–4-10–12 M in the presence of maximum and minimum inhibitor concentrations, probably due to variant types of inhibition from non and uncompetitive. In addition, molecular modeling simulations of targeted compounds revealed their mechanism of action as potent inhibitors for the AChE enzyme.